Factors Associated with the Incidence of Hypertension in the Elderly at the Millenium Clinic in Medan - Maria Haryanti Butarbutar; Zulfikar; Ani Deswita Chaniago; Agnes Ferusgel; Noami Isabella Hutabarat (Institute of Computer Science (IOCS), 2021)
Hypertension is a non-communicable disease which is still a global health problem. Hypertension is a condition in which systolic blood pressure ≥ 140 mmHg and diastolic pressure ≥ 90 mmHg on two measurements with an interval of five minutes in a resting state (1). Uncontrolled disease can cause a 7 times greater chance of having a stroke, 6 times greater congestive heart disease, and 3 times greater heart attack is a non-communicable disease which is a very serious health problem today called hypertension.(2).